2023
DOI: 10.3390/vetsci10110659
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Canine Atopic Dermatitis: Breaking the Cycle—A Narrative Review

Beatriz Fernandes,
Susana Alves,
Vanessa Schmidt
et al.

Abstract: Canine atopic dermatitis (cAD) is a common and distressing skin condition in dogs, affecting up to 30% of the canine population. It not only impacts their quality of life but also that of their owners. Like human atopic dermatitis (hAD), cAD has a complex pathogenesis, including genetic and environmental factors. Current treatments focus on managing clinical signs, but they can be costly and have limitations. This article emphasizes the importance of preventing cAD from developing in the first place. Understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 126 publications
0
3
0
Order By: Relevance
“…Atopic dermatitis is still a complex, incurable disease affecting a large population of dogs, leading to a marked reduction in quality of life for both dogs and their owners, causing emotional and financial strain [ 19 , 42 ]. Nucleotides could potentially serve many different clinical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atopic dermatitis is still a complex, incurable disease affecting a large population of dogs, leading to a marked reduction in quality of life for both dogs and their owners, causing emotional and financial strain [ 19 , 42 ]. Nucleotides could potentially serve many different clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Canine atopic dermatitis (CAD) shares many similarities with atopic dermatitis in people because, in both cases, skin barrier impairment, cutaneous dysbiosis, and immunological dysfunction are key elements involved in its pathogenesis [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. CAD requires long-term management, combining topical and systemic therapies, which often results in a highly complex and expensive regime for pet owners [ 19 ]. This causes not only discomfort and distress for the dog but also generates stress and a negative impact on the quality of life of the pet’s owner [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wipes used in this study were well tolerated as no adverse effect was reported over 14 days. While antiseptics are typically favoured for addressing acute flares of atopic dermatitis, long-term management of chronic cases necessitates a comprehensive approach focused on enhancing skin and coat hygiene, to reinforce the skin barrier and limit the development of skin dysbiosis [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%